2017
DOI: 10.1186/s13068-017-0746-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of environmental bacterial communities as a factor affecting the growth of duckweed Lemna minor

Abstract: BackgroundDuckweed (family Lemnaceae) has recently been recognized as an ideal biomass feedstock for biofuel production due to its rapid growth and high starch content, which inspired interest in improving their productivity. Since microbes that co-exist with plants are known to have significant effects on their growth according to the previous studies for terrestrial plants, this study has attempted to understand the plant–microbial interactions of a duckweed, Lemna minor, focusing on the growth promotion/inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 50 publications
0
66
0
Order By: Relevance
“…In plant-microbe mutualisms, we generally see positive correlations between host and symbiont fitness (Friesen, 2012), although some environments may decouple them (Weese et al, 2015; Shantz et al, 2016). Aquatic microbes associated with duckweed species that may affect growth are known to include diatoms (Desianti, 2012), nitrogen-fixing cyanobacteria (Zuberer, 1982; Duong and Tiedje, 1985; Eckardt and Biesboer, 1988), and a collection of additional bacteria, including members of other nitrogen-fixing clades (Underwood and Baker, 1991; Ishizawa et al, 2017b), and one that may provision phosphorus (Ishizawa et al, 2017a). Here we find positive correlations between duckweed fitness and microbial growth across treatments (Figure 3), potentially indicating positive fitness feedbacks (Sachs et al, 2004) between duckweed and the community of microbes that live on them.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In plant-microbe mutualisms, we generally see positive correlations between host and symbiont fitness (Friesen, 2012), although some environments may decouple them (Weese et al, 2015; Shantz et al, 2016). Aquatic microbes associated with duckweed species that may affect growth are known to include diatoms (Desianti, 2012), nitrogen-fixing cyanobacteria (Zuberer, 1982; Duong and Tiedje, 1985; Eckardt and Biesboer, 1988), and a collection of additional bacteria, including members of other nitrogen-fixing clades (Underwood and Baker, 1991; Ishizawa et al, 2017b), and one that may provision phosphorus (Ishizawa et al, 2017a). Here we find positive correlations between duckweed fitness and microbial growth across treatments (Figure 3), potentially indicating positive fitness feedbacks (Sachs et al, 2004) between duckweed and the community of microbes that live on them.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that microbiome variation has complex effects on phenotypes and fitness in an aquatic plant, similar to how microbiome variation affects terrestrial plants. This is despite the fact that duckweed draws a microbiome from the water environment that is less complex than typical terrestrial plant microbiomes (Lundberg et al, 2012; Ishizawa et al, 2017b). As a smaller plant with a simpler microbiome, more manipulative experimentation is possible for duckweed microbiomes than for terrestrial plant microbiomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations